Я познаю мир. Города мира: детская энциклопедия / [Е. О. Чекулаева] - Чекулаева Е. О. (АСТ: Астрель, 1999)
Экземпляры: ф.4 (20140425) / Инвентарный номер: 45734 / Цена: 40.00 / Авт.знак: Я 11 / ГРНТИ: 39.23 / ББК: 26.89я2